2013
DOI: 10.5586/am.2012.013
|View full text |Cite
|
Sign up to set email alerts
|

Rhizocarpon lavatum and R. reductum (Rhizocarpaceae, Ascomycota), two misunderstood taxa found in the Gorce Mts (Polish Carpathians)

Abstract: Based on collections of P. Czarnota deposited in the GPN herbarium, 8 species of <em>Rhizocarpon</em> are reported from the Gorce Mountains. Two of them, <em>R. lavatum</em> and <em>R. reductum</em> are reported from the Gorce Mts for the first time, instead of erroneously determined <em>R. obscuratum</em>. This species was previously misinterpreted due to taxonomic and nomenclatoric uncertainties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…Rozmieszczenie. W polskich Karpat Zachodnich gatunek stwierdzony dotychczas w Beskidzie Żywieckim (Nowak 1998), Tatrach (Flakus 2004(Flakus , 2007 i Gorcach (Matwiejuk 2012). Występuje w Karpatach Południowych i Wschodnich (Ciurchea 1998; Kondratyuk i in.…”
Section: Siedliskounclassified
See 1 more Smart Citation
“…Rozmieszczenie. W polskich Karpat Zachodnich gatunek stwierdzony dotychczas w Beskidzie Żywieckim (Nowak 1998), Tatrach (Flakus 2004(Flakus , 2007 i Gorcach (Matwiejuk 2012). Występuje w Karpatach Południowych i Wschodnich (Ciurchea 1998; Kondratyuk i in.…”
Section: Siedliskounclassified
“…Rozmieszczenie. W polskich Karpatach Zachodnich gatunek znany jedynie z Beskidu Żywieckiego (Matwiejuk 2011) i Gorców (Matwiejuk 2012). Obecnie notowany również w Beskidzie Sądeckim.…”
Section: Siedliskounclassified
“…New to the Augustów Forest. This saxicolous lichen is quite common in Poland [35]. The species grows on stones and pebbles.…”
Section: Rhizocarpon Reductum Th Frmentioning
confidence: 99%
“…Massal. complex, with hyaline and muriform ascospores [35][36][37]. Examination of the specimens upon which R. obscuratum is based revealed that they are mostly referable to the species currently known as R. lavatum.…”
Section: Rhizocarpon Reductum Th Frmentioning
confidence: 99%
See 1 more Smart Citation